PENGARUH NHT BERBANTUAN BOOKLET MIND MAP TERHADAP RESPON DAN HASIL BELAJAR MATERI PENCEMARAN LINGKUNGAN - Lidia, Lidia; Enawaty, Eny; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study were whether was a significantdifferenceof students achievement, to describestudentresponse and to determine effect of mind mapbookletassistedNHT learningmodelon enviromental pollution material. This research used quasi experimental with Nonequivalent Control Group Design.Population in this study were VII class SMPN 11 Pontianak. The research sample were VII D class control andVII E class experimental. Achievement test, questionnaire,observation sheet and interview guidelineswere used to collect data.Achievement were analyzed using Mann Whitney U- test. This indicated that there were a significant difference between studentsachievementtaught using mind mapbookletassistedNHT learningmodeland conventional learning  model. The average percentage of responsetowardmind map booklet was 86,77 which categorized as very high. Mind map bookletassistedNHT learningmodel on enviromental pollution material has 44.84 %  effect on improving students achievement. Keywords: Numbered Heads Together, Booklet Mind Map,Response,Learning Outcomes, Enviromental Pollution